Insecticidal activity of the extracts of Piper retrofractum fruit and Tephrosia vogelii leaf and their mixtures against Crocidolomia pavonana - Djoko Prijono; R. Dewi Ratna Wulan; Ferdi Ferdi; Nur Alfi Saryanah (CROPSAVER, 2020)
This laboratory work was carried out to evaluate the insecticidal activity of the extracts of Piper retrofractum (Piperaceae) fruit and Tephrosia vogelii (Fabaceae) leaf and their mixtures against the cabbage head caterpillar, Crocidolomia pavonana. Ground plant materials of the two plant species were extracted separately with n-hexane and methanol. The results of leaf-residue feeding bioassays showed that P. retrofractum (Pr) and T. vogelii (Tv) hexane extracts had strong insecticidal activity against C. pavonana larvae (LC95 < 0.5%) and were more active than their respective methanol extracts. Pr and Tv hexane extract had a moderate and a rather weak contact effect on C. pavonana larvae, respectively. In feeding tests, Pr + Tv (1:1) hexane and methanol extract mixtures indicated synergistic joint effect both at LC50 and LC95 level, whereas in the contact test, the mixture of Pr + Tv (1:1) hexane extract was synergistic at the LC50 level but antagonistic at the LC95 level. In choice tests, antifeedant effects of Pr and Tv hexane extracts at LC25 to LC70 levels on C. pavonana larvae followed a concentration-dependent fashion. Thus, separate or mixed P. retrofractum and T. vogelii extracts are potential alternatives for the control of C. pavonana.